Mycoparasitism Activity Of Trichoderma Harzianum Associated With Chitinase Expression Against Ganoderma Boninense - Naher, Laila; Yusuf, Umi Kalsom; Habib, Sheikh Hasna; Huynh, Ky; Shafiquzzaman, Siddiquee
The filamentous fungus Trichoderma is an important fungus due to its biocontrol properties. This study was conducted on mycoparasitism activity of Trichoderma harzianum T32 against Ganoderma boninense upm001 on the basis of Potato Sucrose Agar (PSA) under the scanning electron microscope observation or cell wall degrading enzyme of chitinase gene expression by reverse-transcriptase (RT) PCR. The mycoparasitism process of Trichoderma harzianum T32 showed the coiling or killing of the Ganoderma boninense upm001 in PSA media. Deformity and shrinkage of Ganoderma mycelia was also observed under the scanning microscope in presence of Trichoderma. The RT-PCR profile showed that chitinase gene was expressed during the mycoprasitism activity in T. harzianum against G. boninense. It could be concluded that chitinase gene was an important element in process of biocontrol activity of Trichoderma as the gene was expressed against G. boninense.